Second-Order Elliptic Equation with Singularities - Hichem Boughazi (International Journal of Differential Equations)
On the compact Riemannian manifold of dimension n≥5, we study the existence and regularity of nontrivial solutions for nonlinear second-order elliptic equation with singularities. At the end, we give a geometric application of the above singular equation.